Capital movements : the experience of Commonwealth Caribbean Countries, 1970-84 - Ramsarran, Ramesh (UWI. Institute of International Relations St AugustineTT, 1986)
Examines the current account performance of Commonwealth Caribbean countries and their main sources of finance since 1970. Outlines experiences of individual countries with respect to capital movements. Discusses major forms of capital flows such as foreign private direct investment and government borrowing.